INTERTROCHANTERIC HIP FRACTURES AND VITAMIN D DEFICIENCY; A SIGNIFICANT ASSOCIATION - Jamal, Abdul Basit; Khan, Muhammad Noah Hasan; Sadiq, Marium (Journal of Ayub Medical College Abbottabad, 2021)
Background: Intertrochanteric fractures are a common cause of disability, morbidity and mortality in aged population across the globe. The same population is also vulnerable to ill effects of vitamin D deficiency and presence of multiple comorbidities. Very few studies have been done in our part of the world to find the association of vitamin D deficiency with type of intertrochanteric fractures. Methods: This cross-sectional study was conducted during July 2019 to June 2020 at tertiary care hospital in the megacity of Lahore, Pakistan. Demographic variables were recorded and anteroposterior and lateral views of plain radiographs were used to classify the fractures. History of chronic illness was taken and confirmed with available prescription. Vitamin D level was measured using standard laboratory techniques. Data was entered into IBM SPSS Statistics (version 25) software and analysed. Results: Mean age for males was 65 years and for females 71 years. Boyd and Griffin type II fracture was most common injury (62%). 67% of our study population was suffering from some degree of vitamin D deficiency. Results have shown the significant association of vitamin D deficiency and severity of intertrochanteric fractures (p <0.05). There was no significant difference of degree of vitamin D deficiency and injury pattern among both genders. Conclusion: There is a strong association between degree of vitamin D deficiency and type of intertrochanteric fractures. Our study also highlighted the importance of mechanism of injury, age and presence of diabetes in association with these fractures.